Metabolic profile and safety of piperlongumine - Moreira, Fernanda de Lima; Habenschus, Maisa D.; Barth, Thiago; Marques, Lucas M. M.; Pilon, Alan Cesar [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Vessecchi, Ricardo; Lopes, Norberto P.; Oliveira, Anderson R. M. de (Nature Publishing Group, 2016)
Piperlongumine (PPL), a natural plant product, has been extensively studied in cancer treatment going up on clinical trials. Since the first report related to its use on cancer research (in 2011) around 80 papers have been published in less than 10 years, but a gap still remaining. There are no metabolism studies of PPL in human organism. For the lack of a better view, here, the CYP450 in vitro oxidation of PPL was described for the first time. In addition, the enzymatic kinetic data, the predicted in vivo parameters, the produced metabolites, the phenotyping study and possible piperlongumine-drug interactions in vivo is presented.